2015
DOI: 10.4049/jimmunol.1402512
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular ATP Decrease Mediates NLRP3 Inflammasome Activation upon Nigericin and Crystal Stimulation

Abstract: Activation of the nucleotide-binding oligomerization domain–like receptor family, pyrin domain–containing 3 (NLRP3) inflammasome initiates an inflammatory response, which is associated with host defense against pathogens and the progression of chronic inflammatory diseases such as gout and atherosclerosis. The NLRP3 inflammasome mediates caspase-1 activation and subsequent IL-1β processing in response to various stimuli, including extracellular ATP, although the roles of intracellular ATP (iATP) in NLRP3 activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 32 publications
1
54
3
1
Order By: Relevance
“…It competes with glucose in the glycolytic pathway. When we treated primed BMDMs with 2-DG, we observed dose-dependent induction of IL-1β by ELISA (Figure 6D), as well as cleaved IL-1β p17 and caspase-1 p10 in the supernatant (Figure 6E), as has recently been reported by others (Nomura et al, 2015). However, 2-DG does not function as an inhibitor of hexokinase like NAG or G6P.…”
Section: Resultssupporting
confidence: 87%
“…It competes with glucose in the glycolytic pathway. When we treated primed BMDMs with 2-DG, we observed dose-dependent induction of IL-1β by ELISA (Figure 6D), as well as cleaved IL-1β p17 and caspase-1 p10 in the supernatant (Figure 6E), as has recently been reported by others (Nomura et al, 2015). However, 2-DG does not function as an inhibitor of hexokinase like NAG or G6P.…”
Section: Resultssupporting
confidence: 87%
“…Also NLRP3 inflammasome activation was not due to loss of mitochondrial integrity, as mitochondrial membrane potential was maintained following PGN administration. Interestingly, this effect is distinct from a previous study that found 2-DG reduced mitochondrial membrane potential in macrophages (Nomura et al, 2015). Another mechanism could be mitochondrial DNA (mtDNA) release, as increased mtDNA was evident in the cytosol in response to PGN.…”
contrasting
confidence: 99%
“…Although previously observed (Nomura et al, 2015), this result contrasts with studies demonstrating that blocking glycolysis with 2-DG can inhibit IL-1β activation (O’Neill and Pearce, 2016; Tannahill et al, 2013). It is conceivable that differences in stimulation conditions, 2-DG concentration, level of cell death, or the timing of hexokinase inhibition could explain these differential effects.…”
contrasting
confidence: 98%
“…Other studies have indicated the application of MUC to raise intracellular ROS levels. However, the relationship between intracellular K + level changes and ROS generation remains unknown, and future studies are expected to resolve this issue [27, 28]. Elevation of intracellular ROS mediates the detachment of thioredoxin-interacting protein (TXNIP) from thioredoxin and enables TXNIP to associate with NLRP3, leading to NLRP3 inflammasome activation [29, 30].…”
Section: Inflammation Occurrence Related To Ua Metabolismmentioning
confidence: 99%